Cultivo consorciado de milho com amendoim forrageiro e calopogônio e os efeitos na cultura da soja em rotação - Correia, Nubia Maria [UNESP]; Fuzita, Welder Eduardo; Daniel, Bruno [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
This work aimed to study the intercropping of corn with Arachis pintoi cv. MG-100 and Calopogonium muconoides, regarding to vegetative growth and corn yield, capacity of production of forage dry matter, infestation of weeds and the effect of this system of production in the soybean crop in rotation. This research was carried out under field conditions form December 2008 to April 2010 in the UNESP, Campus of Jaboticabal, São Paulo State, Brazil. The experiment was arranged in a randomized block in split-plot design with four replications. Two forages species (A. pintoi and C. muconoides), four amounts of seeds (400, 800, 1200 e 1600 points of cultural value ha(-1)) and one treatment additional with single corn were studied. The intercropping did not affect the vegetative growth and corn yield when compared to the single corn. The C. muconoides had greater density and dry matter of plants than A. pintoi. The number of plants and dry matter of C. muconoides increased with increasing the amount of seeds sowed in the area. These variables were not affected by the sowing density of A. pintoi. The straw production by the forage species before of the soybean crop in rotation was inexpressive (less than 1100 kg ha(-1)). The intercropping did not affect the weed occurrence and the development of the soybean crop in rotation.
Intercropping of corn with Arachis pintoi and Calopogonium muconoides and the effect on the soybean crop in rotation
Keywords: Glycine max; crop-livestock; No-tillage; Zea mays